Rapid diagnosis of non-tuberculous mycobacterial pulmonary diseases by metagenomic next-generation sequencing in non-referral hospitals - Wang, Jing; Xu, Huan; Wang, Xi; Lan, Jian (Frontiers in Cellular and Infection Microbiology, 2023)
Objectives The incidence of non-tuberculous mycobacterial pulmonary disease (NTM-PD) has increased steadily globally, but the current culture-based diagnosis of NTM-PD is difficult and time-consuming, leading to a high possibility of misdiagnosis. Therefore, new methods should be introduced to improve the processes for clinical diagnosis of this disease. Methods Our retrospective observational study enrolled 12 NTM-PD patients who were identified by way of metagenomic next-generation sequencing (mNGS), as well as the characteristic radiological presentation of slowly progressed, usually concomitant bronchiectasis, small cavitary opacity, and multiple nodules that respond poorly to empirical antibiotic therapy. These patients received the recommended drug regimen based on the identified non-tuberculous mycobacteria (NTM) species. Clinical data, including symptoms, laboratory tests, dynamic computed tomography imaging, treatment, and outcome, were recorded and analyzed. Results The results of mNGS were all positive, with the standard specifically mapped read numbers (SDSMRN) of NTM ranging from 1 to 766; this was confirmed in six patients via quantitative polymerase chain reaction (qPCR) analysis. The duration fromsample collection tomNGS results was 1–4 days. Among our 12 patients (except for one lost to follow-up) the CT imaging for 11 patients showed significant absorption of lesions. Conclusions Our results draw attention to NTM infection as a possible cause of community-acquired pneumonia, especially in patients with suggestive radiological presentation and poor responses to empirical antibiotic therapy. Our study also indicated that mNGS represented a potentially effective tool for the rapid identification of NTM in the respiratory sample. Improved clinician awareness combined with the utilization of mNGS could guide earlier diagnosis and targeted treatment, and finally improved the prognoses of patients with NTM-PD.